Impact of PCU Values on Performance Assessment of Unsignalized Intersection: Case Study of Airport Chowk, Surkhet - Katuwal, Arjun; Gautam, Santosh; Tiwari, Hemant (Mid-West University Journal of Engineering & Innovation, 2025)
Airport Chowk Intersection is an unsignalized intersection which is one of the main intersections of Birendranagar, Surkhet which faces heavy traffic flow during peak hours. This study aims to find the Volume-to-Capacity ratio and level of services at the intersection using the passenger car unit ( PCU) value based on the Indo Highway Capacity Manual (Indo-HCM) 2017, Nepal Road Standard 2070 (NRS) and Department of Road (DOR) and to compare the results obtained from all three standards. Classified traffic volume count is conducted to determine the peak hour volume. Peak hour traffic volume is converted into PCU based on all three standards. The intersection is assessed using the methodology recommended by Indo-HCM for the assessment of unsignalized intersections. Conflicting flow rates and critical gap values are determined for each movement in priority rank. Thereafter intersection’s capacity and Level of Service (LOS). The result indicates that the intersection operates at an overall LOS of ‘A’ in the morning peak hour for movement 1 (Pipira to Airport) but ‘B’ in the morning and ‘C’ in the evening for movement 3 (Airport to Bulbule). Remarkably, movement 3 experiences higher congestion because of the greater proportion of heavy vehicles resulting in an increase in critical gaps and V/C ratios. By comparing the value of LOS obtained from PCU based on all three standards found almost similar except value of LOS obtained from NRS for movement in the evening peak hour. The study highlights the necessity of strategic interventions to enhance intersection performance and mitigate congestion during peak hours.